2014
DOI: 10.1002/j.1532-2149.2014.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

The rubber hand illusion increases heat pain threshold

Abstract: The RHI increases heat pain threshold and the analgesic effect of the RHI is comparable with that of seeing one's own hand. The latter finding may have clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 23 publications
4
52
0
Order By: Relevance
“…However, in disagreement with Mohan's finding are the results of another RHI-pain study. Using three conditions in a within subjects design, Hegedus and collaborators found that both RHI and vision of the own hand resulted in slightly (but significantly) higher pain thresholds, compared to the asynchronous stroking control condition (Hegedüs et al, 2014). Similar findings were found in a study investigating the effects of the RHI on the perceived discomfort caused by cold stimuli.…”
Section: Rubber Hand Illusion and Painmentioning
confidence: 55%
“…However, in disagreement with Mohan's finding are the results of another RHI-pain study. Using three conditions in a within subjects design, Hegedus and collaborators found that both RHI and vision of the own hand resulted in slightly (but significantly) higher pain thresholds, compared to the asynchronous stroking control condition (Hegedüs et al, 2014). Similar findings were found in a study investigating the effects of the RHI on the perceived discomfort caused by cold stimuli.…”
Section: Rubber Hand Illusion and Painmentioning
confidence: 55%
“…This is reminiscent of the so‐called rubber hand illusion (RHI, Botvinick and Cohen, ), in which perceived ownership over an artificial limb can be induced via the congruence of vision and touch. There is evidence that the RHI may reduce pain (Hegedüs et al., ; Martini et al., ; Siedlecka et al., ). It remains to be shown to what extent some of the divergent results can be explained by methodological differences (Mohan et al., ; Nierula et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…somatosensory input from the skin of the real hand (out of view) and visual input from the eyes watching the rubber hand being stroked. The cerebrum appears to attribute stronger reliance on the visual frame of reference to generate a final perceptual experience that involves distortion of position sense (proprioceptive drift) of the real hand which is relocated to the space occupied by the rubber hand [33] [9,34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that perceived body ownership may increase pain threshold and decrease pain intensity to experimentally induced pain [34,35], although Mohan et al [33] found that pain threshold was not affected during the rubber hand illusion (in view) when the real hand (out of view) received noxious thermal stimuli. Chang et al [36] found that the sympathetic response to acupuncture needle stimulation was influenced by visual expectation rather than by modifications of body ownership producing greater sympathetic responses measured by skin conductance.…”
Section: Discussionmentioning
confidence: 99%